Empowering Islamic social finance through zakat fund in realization of sustainable development goals SDGS وظيف التمويل االجتماعي اإلسالمي من خالل الزكاة في تحقيق أهداف التنمية المستدامة: - Zakariyah, Habeebullah (Lembaga Zakat Negeri Kedah, 2019)
Islamic social Finance (zakat, waqf, sadaqah, Qard Hasan etc.) is one of the most effective ways to meet the needs of the society and attends to people's daily demands. This paper seeks to explicate the role of zakat in achieving sustainable development goals SDGs, and to determine its scope in SDGs 2030 as presently ratified by most of the nations across the globe. This goal is a conceptual agenda of the United Nations which covers three main aspects: The Economic, social and the environmental. The researcher adopts critical analytical study to discuss the views of classical and contemporary scholars on the extent of using zakat to achieve SDGs 2030. The study found that Islamic social finance has a major role in attaining some of the SGGs, and that the higher objective of zakat is in line with the aim of societal care, including poverty eradication, attending to needy people, and helping students. Despite this focus on the higher objective of zakat on one hand, and sustainable development goals on the other hand except that the zakat is divine in nature unlike the sustainable development goals. The study recommends that researchers, experts in zakat and its institutions should explore the possibility of using zakat institutions as an indicator of sustainable development goals.